CRISPR-Cas9: Tool for Qualitative and Quantitative Plant Genome Editing - Noman, Ali; Aqeel, Muhammad; He, Shuilin (Frontiers in Plant Science, 2016)
Recent developments in genome editing techniques have aroused substantial excitement among agricultural scientists. These techniques offer new opportunities for developing improved plant lines with addition of important traits or removal of undesirable traits. Increased adoption of genome editing has been geared by swiftly developing Clustered regularly interspaced short palindromic repeats (CRISPR). This is appearing as driving force for innovative utilization in diverse branches of plant biology. CRISPR-Cas9 mediated genome editing is being used for rapid, easy and efficient alteration of genes among diverse plant species. With approximate completion of conceptual work about CRISPR-Cas9, plant scientists are applying this genome editing tool for crop attributes enhancement. The capability of this system for performing targeted and efficient modifications in genome sequence as well as gene expression will certainly spur novel developments not only in model plants but in crop and ornamental plants as well. Additionally, due to non-involvement of foreign DNA, this technique may help alleviating regulatory issues associated with genetically modified plants. We expect that prevailing challenges in plant science like genomic region manipulation, crop specific vectors etc. will be addressed along with sustained growth of this genome editing tool. In this review, recent progress of CRISPR-Cas9 technology in plants has been summarized and discussed. We reviewed significance of CRISPR-Cas9 for specific and non-traditional aspects of plant life. It also covers strengths of this technique in comparison with other genome editing techniques, e.g., Zinc finger nucleases, Transcription activator-like effector nucleases and potential challenges in coming decades have been described.